Working Behind Wyoming's Carbon Curtain. (May 2015) - Neal, Dan
Dan Neal, formerly the Executive Director of the Equality State Policy Center in Casper, Wyoming, was presented the Lorin Kerr Award by the Occupational Health and Safety Section of the American Public Health Association at its annual meeting in November 2014. The Kerr Award recognizes individuals who have stepped up to provide new leadership in occupational health and safety activism with sustained and outstanding efforts and dedication to improving the lives of workers. (Lorin Kerr [1909–1991] was a life-long activist and served for over forty years as a physician for the United Mine Workers. He was dedicated to improving access to health care for coal miners and other workers and to obtaining compensation for and preventing black lung disease.) Neal's acceptance speech introduces us to the health and safety concerns in Wyoming's expanding energy sector and explains how a coalition for occupational safety and health is organizing to address these concerns.